CDIO implementation in fluid mechanics at UiTM Sarawak: student centered / Beatrice Bidaun ... [et al.] - Bidaun, Beatrice; Nazarudin, Amir; Noh, Narita; Mohd Noor, Siti Nur Aishah (UiTM Cawangan Johor, 2019)
This paper generally discusses the initial implementation of CDIO to Fluid Mechanics, a course in Diploma in Civil Engineering UiTM Sarawak. CDIO has been introduced since 2013 in the Faculty of Civil Engineering as a key driver to ensure students are industry- ready upon graduation. However, the implementation viewed to be still at the surface level due to lack of proper module being introduced for civil engineering courses. This paper highlights and depicts the method of CDIO implementation as a part of learning activities. Preliminary findings indicate that, CDIO has been successfully implemented based on student's performance. Continuous Quality Improvement report reveals student's attainment for CDIO assignment is 84.9% on the average score and 100% passes for 82 students' sample. However, there are rooms for improvement and betterment of the task given as well as preparation of rubric in the future. It is important to continuously monitor the impacts of CDIO in civil engineering courses for student achievement in fostering the generic skills to fulfill modern engineering demand during working life.